ANALISIS PENGARUH TRUST IN ONLINE STORE, PERCEIVED RISK, ATTITUDE TOWARDS ONLINE PURCHASING TERHADAP MINAT BELI KONSUMEN PRODUK FASHION DI SURABAYA - SOEGIARTO, TJIOE AMELIA (Kajian Ilmiah Mahasiswa Manajemen, 2012)
The development of online business in retail industry lead to the consumer’s intention in online shopping. Trust in online store, perceived risk and attitude towards online purchasing are all factors that lead to incerasing consumer’s respond in regards of online purchase intention. The purpose of this study was to investigate the significant impact of trust in online store on perceived risk of fashion products in Surabaya, to determine the significant impact of perceived risk on attitude towards online purchasing of fashion products in Surabaya, and to acknowledge any significantt effects of attitude towards online purchasing on online purchase intention of fashion products in Surabaya. The study design utilize casual study that attempts to reveal relationship and cocrrelation between variables. The research data is the data interval with primary data through questionarres that use 5 likert scale. The Data analysis techniques adopt the path analysis. This study found that Trust in online store affects Perceived risk, Perceived Risk lead to Attitude towards online purchasing, and Attitude towards online shopping significantly influences Online Purchase Intention.